Implementación de una planta de producción de la cadena de suministros del bar estudiantil de la Unidad Educativa Insutec en la ciudad de Quevedo - Gómez Mosquera, Andrea Vanessa (2025)
The supply chain is considered the tool to manage a production area and make the provision of a food service more effective, which influences its availability, freshness and presentation of the products, key aspects to satisfy the customer. An efficient supply chain ensures that the inputs arrive on time and in optimal conditions, allowing the services, as in the case of a restaurant, to meet high quality standards. The proper management of the supply chain allows to reduce waiting times, improve the consistency of the service and respond quickly to demand, aspects that contribute to a superior customer experience and loyalty. This article is carried out with the objective of designing a proposal for improvement through the implementation of a production plant of the supply chain of the student bar of the INSUTEC educational unit in the city of Quevedo. A survey is applied to workers and managers who show that the students' orders cannot be fulfilled due to insufficient materials and resources, in addition, they agree on the need to generate a distribution and logistics system that helps improve the fulfillment of orders. The proposal of a production plant as part of the supply chain will allow the student bar of the INSUTEC educational unit to provide a better-quality service by having the necessary resources and supplies to fulfill student orders.